2009
DOI: 10.3177/jnsv.55.309
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Glutathione Peroxidase, Superoxide Dismutase, Vitamins A, C, E and Malondialdehyde in Patients with Cardiovascular Disease in Zahedan, Southeast Iran

Abstract: Summary Growing evidence has demonstrated that oxidative stress and increased altered oxygen utilization contribute to atherogenesis and cardiovascular disease (CVD) progression. Antioxidants protect the body from damage caused by free radicals. The objective of this study was to determine antioxidants status in CVD patients. This cross-sectional study was performed on 71 patients clinically diagnosed with CVD and 63 healthy individuals. Plasma malondialdehyde (MDA) level was measured for lipid peroxidation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
1
20
2
Order By: Relevance
“…Oxidized LDL is associated with the pathogenesis of atherosclerosis, a key in the early stage of CVD. However, oxidized LDL has a toxic effect on the vascular cells, and the cytotoxic potency of oxidized LDL is related to its content of lipid peroxidation products (20,21). Recent findings show that oxidative stress and lipid peroxidation have a relationship with the pathogenesis of atherosclerosis.…”
Section: Malondialdehyde (Mda)mentioning
confidence: 99%
“…Oxidized LDL is associated with the pathogenesis of atherosclerosis, a key in the early stage of CVD. However, oxidized LDL has a toxic effect on the vascular cells, and the cytotoxic potency of oxidized LDL is related to its content of lipid peroxidation products (20,21). Recent findings show that oxidative stress and lipid peroxidation have a relationship with the pathogenesis of atherosclerosis.…”
Section: Malondialdehyde (Mda)mentioning
confidence: 99%
“…Serum levels of vitamin E were determined using high pressure liquid chromatography (HPLC) as described previously ( 16 ). Plasma concentration of vitamin C was measured by a spectrophotometric method ( 17 ) as described previously ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…SOD and GPx were measured using commercially available kits supplied by Randox Laboratories Ltd (Randox, UK) as described previously ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have revealed a significant imbalance of pro-oxidants and antioxidants in patients with CKD and diabetes [15,16,19,24,25]. It is also well known that bilirubin shows an antioxidant capacity, as in neonatal patients with increased bilirubin levels [26][27][28].…”
Section: Discussionmentioning
confidence: 99%